The erosion of trust during a global pandemic and how public administrators should counter it - Deslatte, Aaron (American Review of Public Administration)
This article argues that public administrators must advance a more equity-based assessment of vulnerabilities in American communities and more risk-based communication strategies. It provides an overview of partisan motivated reasoning, how this has influenced the response to the coronavirus pandemic. Experimental evidence then demonstrates how the framing of the pandemic can influence trust in various public messengers. The coronavirus pandemic is merely one of the many exigent threats humanity faces today. Public administrators are the planners, engineers, analysts, auditors, lawyers, and managers on the front lines of these existential crises. It is their job to sift through the information environment and$1 (Bhowever boundedly$1 (Btackle problems. For the sake of the American democracy, public administrators need to regain the people$1 (Bs trust. They could start by leveling with them about the challenges ahead. - Reproduced s
Keywords: Risk communication, COVID-19, Trust, Motivated reasoning, Climate change